Effects of Styrenic Comonomers in the Metallocene Catalyzed Terpolymerization - Yoon1, G.L.; Yang1, D.J.; Kim2, H.J.; Lee1, J.C.; Park1, N.H.; Kim1, D.H. (Asian Journal of Chemistry, 2013)
Various terpolymers consisting of ethylene, 1-hexene and styrenic monomer were synthesized using a metallocene catalyst and cocatalyst system. The styrenic monomer, as the third monomer, was styrene, p-methyl styrene or 4-tert-butyl styrene. The structures of the terpolymers were examined by 13C NMR and 1H NMR spectroscopy. The catalytic activity, polymer yield and molecular weights of the terpolymers were compared. The effects of each alkyl substituent of the styrenic monomer on the kinetics and thermal properties of the terpolymers, which were synthesized under identical polymerization conditions, were examined. The mechanical properties of the terpolymers were observed using a universal testing machine. The Shore A hardness, scratch resistance, permanent tensile strain, glass transition, crystallization temperature and the density of the terpolymers were also measured.